EFEKTIVITAS MODEL QUANTUM TEACHING DENGAN PENDEKATAN REALISTIK UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI BANGUN RUANG - Arifuddin, Ahmad (PD PGMI se Indonesia, 2017)
This research is an experimental research using pretest-posttest control group design that aims to know the effectiveness of quantum teaching model with realistic approach in learning mathematics on the geometryÂ material. The techniques of data collection in this study are documentation, observation, and test. Meanwhile, the instruments used are test sheets and observation sheets. While the techniques of data analysis used in this study are classical completeness test, comparative test (mean difference test), and test improvement (n-gain test). The results of this study indicate that (1) the learning outcomes of students exceed the KKM, which obtained an average value of 77.70 with 85.18% classical completeness; (2) the average value of posttest experimental class of 77.70 is better than control class of 69.07; (3) improvement of learning outcomes of students in the experimental class experienced a significant increase, ie by 0.42.